Advances in Parallel & Distributed Processing, and Applications Proceedings from PDPTA'20, CSC'20, MSV'20, and GCC'20 - Arabnia, Hamid R.; Deligiannidis, Leonidas; Grimaila, Michael R.; Hodson, Douglas D.; Joe, Kazuki; Sekijima, Masakazu; Tinetti, Fernando G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
The book presents the proceedings of four conferences: The 26th International Conference on Parallel and Distributed Processing Techniques and Applications (PDPTA'20), The 18th International Conference on Scientific Computing (CSC'20); The 17th International Conference on Modeling, Simulation and Visualization Methods (MSV'20); and The 16th International Conference on Grid, Cloud, and Cluster Computing (GCC'20). The conferences took place in Las Vegas, NV, USA, July 27-30, 2020. The conferences are part of the larger 2020 World Congress in Computer Science, Computer Engineering, & Applied Computing (CSCE'20), which features 20 major tracks. Authors include academics, researchers, professionals, and students. Presents the proceedings of four conferences as part of the 2020 World Congress in Computer Science, Computer Engineering, & Applied Computing (CSCE'20); Includes the research tracks Parallel and Distributed Processing, Scientific Computing, Modeling, Simulation and Visualization, and Grid, Cloud, and Cluster Computing; Features papers from PDPTA 20, CSC 20, MSV 20, and GCC 20.
Introduction -- PDPTA 2020 -- Big Data and High-Performance Computing -- Parallel/Distributed Applications -- Parallel/Distributed Architectures -- Networks and Interconnection Networks -- Energy/power-aware Computing -- Reliability and Fault-tolerance -- Building Block Processors -- Real-time and Embedded Systems -- Parallel/Distributed Algorithms -- Multimedia Communications, Systems, and Applications -- CSC 2020 -- ALGORITHMS AND METHODS -- HIGH PERFORMANCE COMPUTING & COMMUNICATION SYSTEMS -- MODELING, SIMULATION & VISUALIZATION METHODS -- BIG DATA AND DATA ANALYTIC -- MSV 2020 -- Visualization of Big Data -- Information and Scientific Visualization -- Visual Interactive Simulation and Modeling -- Visualization Tools and Systems for Simulation and Modeling -- Virtual Reality and Simulation -- Virtual Environments and Data Visualization -- Simulation Languages -- Modeling and Simulation for Education and Training -- GCC 2020 -- CLOUD COMPUTING -- GRID COMPUTING -- CLUSTER COMPUTING -- Conclusion.
Keywords: Telecommunication; Engineering mathematics; Artificial intelligence; Computational intelligence; Communications Engineering, Networks; Engineering Mathematics; Artificial Intelligence; Computational Intelligence